Psychological Well – Being in Physical Education & Sport Sciences College Students - Hassan, Asaad; Jasem, Wasan (Journal of Physical Education, 2020)
The aim of the research is to identify the level of psychological well–being that can be a reason for students’ success in theoretical and application classes during their college years as well as identifying its effect on lifestyle. The researchers used the descriptive method on (307) student from physical education and sport sciences by designing a scale for psychological well – being. The final scale consisted of (56) item distributed in six fields (life satisfaction, self – independence, social relationships, personal development, self – acceptance, calmness). The scale was applied to (300) students to collect the data and come up with conclusion. The researchers concluded that most students have moderate levels of psychological well–being due to economical, psychological, and health difficulties that made their levels moderate.